PENINGKATAN MOTIVASI BELAJAR BAHASA INDONESIA MELALUI PEMBELAJARAN BERBASIS PORTOFOLIO SISWA KELAS IV SDN KEBONSARI 01 KEC. KEBONSARI MADIUN TAHUN PELAJARAN 2011/2012 - Muchsin Muchsin (IKIP PGRI MADIUN, 2015)
Some linguists argue about the definition of reading, WJS Poerwodarminto (1976: 71) says that reading is seen while express an article with the aim to determine its contents. Another opinion expressed by Kastowo (1978: 1) that reading is catching an understanding through writing. Based on the above opinion, the reading reveals not only writing but also understanding the text. The formulation of this research as follows: